Pharmacokinetics of mycophenolate mofetil and its glucuronide metabolites in healthy volunteers. (July 2008) - Léévesque, Eric; Benoit-Biancamano, Marie-Odile; Delage, Robert; Couture, Féélix; Guillemette, Chantal
We previously reported that polymorphisms in the UGT2B7 and UGT1A9 genes are associated with significant alteration in the disposition of mycophenolic acid (MPA) in healthy volunteers.Aim: This study further evaluates the impact of genetic polymorphisms at the UGT1A1, UGT1A7 and ABCC2 loci.Methods: Genetic analyses of five UGT candidate genes and ABCC2 were completed on 47 healthy subjects who received a single dose of 1.5 g mycophenolate mofetil and completed a 12-h pharmacokinetic profile.Results: Multivariate analyses indicate that the ABCC2 -24T promoter polymorphism is associated with a 25% increase in acyl mycophenolic acid phenolic glucuronide level. Subjects with combined ABCC2 -24T and UGT1A9*3 genotypes present a 169% increased exposure to AcMPAG. Homozygosity for UGT1A7 387G/391A (129Lys/131Lys) is associated with a modest but significant 7% reduction in MPA level. When these additional genetic factors are considered in the model, the effects of previously described UGT1A9 and UGT2B7 variations remain significant. No significant effect is observed for UGT1A1*28, UGT1A7 622T/C (Trp208Arg), UGT1A9 -440TC/-331CT, UGT1A9 -118 TA9/10 and seven other ABCC2 SNPs.Conclusion: We demonstrate that MPA disposition is a multigenic process, and that additional studies are required to ascertain the relationship between UGT, ABCC2 genotypes and MPA pharmacokinetics in transplant recipients.